Role of Rbp1 in the Acquired Chill-Light Tolerance of Cyanobacteria - Tan, Xiaoming (American Society for Microbiology, 2011)
Synechocystis sp. strain PCC 6803 cultured at 30°C losses viability quickly under chill (5°C)-light stress but becomes highly tolerant to the stress after conditioning at 15°C (Y. Yang, C. Yin, W. Li, and X. Xu, J. Bacteriol. 190:1554–1560, 2008). Hypothetically, certain factors induced during preconditioning are involved in acquisition of chill-light tolerance. In this study, Rbp1 (RNA-binding protein 1) rather than Rbp2 was found to be accumulated during preconditioning, and the accumulation of Rbp1 was correlated with the increase of chill-light tolerance. Inactivation of its encoding gene rbp1 led to a great reduction in the acquired chill-light tolerance, while ectopic expression of rbp1 enabled the cyanobacterium to survive the chill-light stress without preconditioning. Microarray analyses suggested that the Rbp1-dependent chill-light tolerance may not be based on its influence on mRNA abundance of certain genes. Similarly to that in Synechocystis, the Rbp1 homologue(s) can be accumulated in Microcystis cells collected from a subtropic lake in low-temperature seasons. Rbp1 is the first factor shown to be both accumulated early during preconditioning and directly involved in development of chill-light tolerance in Synechocystis. Its accumulation may greatly enhance the overwintering capability in certain groups of cyanobacteria.